Integrating Technical Studies Into Elementary Education: A Pathway to Holistic Learning in Nigeria - Isaac, John Ibanga; Yusuf, Mohammed Adamu; Sulisworo, Dwi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2024)
The main aim of the study was to investigate the integration of technical studies into elementary (primary) education as a pathway to holistic learning in Nigeria. The population of the study was 291,015 comprising 18,796 public primary school teachers, 268,430 parents, and 3789 Education Supervisors from the Ministry of Education in the six states of the Northeast. The study adopted Simple random sampling and a sample size of 379 respondents was determined using Krejcie and Morgan's (1970) sample size table. A structured questionnaire was utilized to gather data for the study. The questionnaire was validated by three experts and a reliability index of 0.86 was obtained using Cronbach Alpha after a trial test. The data for the study was analyzed using mean and standard deviation to answer the research questions while ANOVA was used to test the hypotheses at 0.05 level of significance. The study revealed that technical studies for Nigerian primary schools should include Digital Literacy, Engineering and Design, Digital Creativity, Applied Science and Technology, and Computational Thinking and Problem Solving Technical studies are instrumental in enhancing pupils' skills across various domains, aligning with educational research that emphasizes their practical benefits Technical studies are instrumental in enhancing pupils' skills across various domains, aligning with educational research that emphasizes their practical benefits.